2004
DOI: 10.1037/1528-3542.4.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Affective Evaluation Does Not Automatically Predispose for Arm Flexion and Extension.

Abstract: Affect may have the function of preparing organisms for action, enabling approach and avoidance behavior. M. Chen and J. A. Bargh (1999) suggested that affective processing automatically resulted in action tendencies for arm flexion and extension. The crucial question is, however, whether automaticity of evaluation was actually achieved or whether their results were due to nonautomatic, conscious processing. When faces with emotional expressions were evaluated consciously, similar effects were obtained as in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
262
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(305 citation statements)
references
References 51 publications
29
262
14
Order By: Relevance
“…First, consistent with previous literature (Bamford & Ward, 2008;Chen, M and Bargh, 1999;De Houwer et al, 2001;Duckworth et al, 2002;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura et al, 2000) we see a reaction time (RT) congruency effect: participants are faster to approach than avoid pleasant emotional stimuli, but faster to avoid than approach unpleasant stimuli. This reflects the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and the additional effort required to regulate these tendencies when required.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…First, consistent with previous literature (Bamford & Ward, 2008;Chen, M and Bargh, 1999;De Houwer et al, 2001;Duckworth et al, 2002;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura et al, 2000) we see a reaction time (RT) congruency effect: participants are faster to approach than avoid pleasant emotional stimuli, but faster to avoid than approach unpleasant stimuli. This reflects the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and the additional effort required to regulate these tendencies when required.…”
Section: Discussionsupporting
confidence: 78%
“…Participants have faster reaction times (RT) when performing congruent than performing incongruent actions. This confirms the automatic predisposition to approach pleasant and avoid unpleasant stimuli, and highlights the additional effort needed to regulate these tendencies when required (Bamford & Ward, 2008;Chen & Bargh, 1999;De Houwer, Crombez, Baeyens, & Hermans, 2001;Duckworth, Bargh, Garcia, & Chaiken, 2002;Krieglmeyer, De Houwer, & Deutsch, 2012;Neumann & Strack, 2000;Rotteveel & Phaf, 2004;Solarz, 1960;Wentura, Rothermund, & Bak, 2000). The difference in the speed of the response on congruent compared to the incongruent trials has been termed a congruency effect; for example a large congruency effect would be observed when comparing congruent trials with very fast responses to incongruent trials with very slow responses, whereas more similar response times for congruent and incongruent trials would represent a smaller congruency effect.…”
Section: Introductionmentioning
confidence: 53%
“…In contrast to the arousal pattern evidenced in the MEP data, RT and force data followed a valence-specific pattern of activity and replicated previous evidence by revealing a facilitation effect when unpleasant images, as compared with pleasant and neutral images, were combined with extension movements (Chen & Bargh, 1999;Coombes et al, 2007aCoombes et al, , 2007bRotteveel & Phaf, 2004). This finding supports the long-held notion that emotions prime the human body for action (Ekman & Davidson, 1994;Frijda, 1986Frijda, , 2009Frijda et al, 1989;Izard, 1994).…”
Section: Valence Effects On Rt and Forcesupporting
confidence: 54%
“…To assimilate previous TMS findings that have shown an arousal effect on CST excitability (Baumgartner et al, 2007;Hajcak et al, 2007) and behavioral findings that have shown a valence effect on motor output (Chen & Bargh, 1999;Coombes et al, 2006Coombes et al, , 2007aCoombes et al, , 2007bCoombes, Janelle, & Duley, 2005;Rotteveel & Phaf, 2004), in the present study, we examined how viewing emotional images while engaging the motor system via the preparation of a ballistic extension movement would modulate CST excitability. Pursuant to this aim and to replicate a previously used behavioral protocol (Coombes et al, 2007a(Coombes et al, , 2007b, we held the direction of the required movement constant (i.e., extension) and manipulated emotional state through the presentation of pleasant, unpleasant, and neutral images.…”
mentioning
confidence: 99%
“…It has been noted that both fear and disgust often include behavioural components of withdrawal (e.g., [20,40]). Unpleasant cues activate the defensive system (i.e., danger, fear), which facilitates movements away from the cue (e.g., [8,47]). Ekman claims that in case of fear withdrawal entails escaping from the threatening stimulus.…”
Section: Movementmentioning
confidence: 99%